Pengaruh Media Video Edukasi terhadap Pengetahuan Mengenai Anemia dan Kepatuhan Konsumsi Tablet Tambah Darah pada Siswi SMA Taman Madya 5 - Romadhona, Nur Afiah; Khasanah, Tri Ardianti (Media Gizi Ilmiah Indonesia, 2025)
Anemia is a condition where the concentration of red blood cells that carry oxygen is inadequate. Iron deficiency is considered the most common cause of anemia. This study aims to analyze the impact of educational video media on knowledge about anemia and compliance with iron supplement intake among female students at SMA Taman Madya 5. The research method used was a quasi-experimental pre-post test with a control group design. The sample consisted of 11th-grade students at SMA Taman Madya 5, divided into two groups, each containing 18 students in the treatment and control groups, selected through purposive sampling. Analysis using the Wilcoxon and McNemar tests showed a significant difference in knowledge (p-value = 0.014) and compliance (p-value = 0.016) before and after the intervention with educational video media. The Mann-Whitney test analysis showed no significant difference in average knowledge (p-value = 0.067) before and after the intervention with pamphlet media. In conclusion, there was no difference in the average knowledge about anemia and compliance with iron supplement intake between the two groups. However, there was a higher increase in knowledge and compliance scores in the intervention group that used educational video media compared to the control group with pamphlet media.